Association of dietary inflammatory index with liver fibrosis and fatty liver index in a population with metabolic dysfunction-associated steatotic liver disease: A cross-sectional study - Sang, Ziqi; Wang, Han; Leng, Yan; Huang, Xupeng; Sun, Peng; Wang, Ruolin; Liu, Tiejun; Deng, Houbo (Frontiers in Nutrition, 2025)
BackgroundHepatic fibrosis and the fatty liver index (FLI) are critical indicators for assessing the progression and severity of metabolic dysfunction-associated steatotic liver disease (MASLD) and serve as valuable reference markers for predicting MASLD-related risks. The Dietary Inflammation Index (DII) quantifies the inflammatory effects of dietary intake and has been extensively utilized in nutritional and epidemiological studies. Although studies have been conducted to confirm the correlation between dietary quality and MASLD in the general population, this study sought to further explore the association between the DII and key indicators of liver disease severity—namely hepatic fibrosis and the FLI—within a cohort diagnosed with MASLD. In addition, the potential mediating role of the systemic immune inflammatory index (SII) in these associations was also investigated.MethodsThis cross-sectional study was based on data from the 2017–2020 cycles of the U.S. National Health and Nutrition Examination Survey (NHANES), a nationally representative program designed to assess the health and nutritional status of the population. In this study, we analyzed the correlation of DII with FLI and liver fibrosis in a population of patients with MASLD by linear regression, logistic regression, RCS curves and subgroup analysis. A mediation model was applied to assess the potential intermediary effect of SII on the associations between DII, FLI, and hepatic fibrosis.ResultsThe results of this study indicate that, after adjusting for all covariates, the Dietary Inflammatory Index (DII) was not significantly associated with the Fatty Liver Index (FLI) among U.S. adults with MASLD (β = 0.32, 95% CI: −1.393 to 2.034, P = 0.631). Similarly, no significant association was observed between DII and the risk of liver fibrosis (OR = 1.152, 95% CI: 0.885 to 1.499, P = 0.210). Subgroup analyses further demonstrated that these associations were not modified by demographic or metabolic stratification variables, and the relationship appeared to be nonlinear.ConclusionIn U.S. adults with MASLD, no significant association was found between DII and the risk of liver fibrosis or elevated FLI. Although DII is linked to various chronic diseases, its role in MASLD appears limited and non-specific, particularly in capturing intermittent disease progression. No mediating effect of SII was observed. These findings underscore the importance of carefully considering dietary factors in the clinical evaluation of MASLD progression. The potential relationship between diet and liver disease progression warrants further investigation.